Intravenous injection of adipose‐derived mesenchymal stromal cells benefits gait and inflammation in a spontaneous osteoarthritis model. Issue 4 (13th September 2022) - Afzali, Maryam F.; Pannone, Stephen C.; Martinez, Richard B.; Campbell, Margaret A.; Sanford, Joseph L.; Pezzanite, Lynn M.; Kurihara, Jade; Johnson, Valerie; Dow, Steven W.; Santangelo, Kelly S.
Abstract: Osteoarthritis (OA) is a leading cause of morbidity among aging populations, yet symptom and/or disease‐modification remains elusive. Adipose‐derived mesenchymal stromal cells (adMSCs) have demonstrated immunomodulatory and anti‐inflammatory properties that may alleviate clinical signs and interrupt disease onset and progression. Indeed, multiple manuscripts have evaluated intra‐articular administration of adMSCs as a therapeutic; however, comparatively few evaluations of systemic delivery methods have been published. Therefore, the aim of this study was to evaluate the short‐term impact of intravenous (IV) delivery of allogeneic adMSCs in an established model of spontaneous OA, the Hartley guinea pig. Animals with moderate OA received once weekly injections of 2 × 10 6 adMSCs or vehicle control for 4 weeks in peripheral veins; harvest occurred 2 weeks after the final injection. Systemic administration of adMSCs resulted in no adverse effects and was efficacious in reducing clinical signs of OA (as assessed by computer‐aided gait analysis) compared to control injected animals. Further, there were significant decreases in key inflammatory mediators (including monocyte chemoattractant protein‐1, tumor necrosis factor, and prostaglandin E2 ) both systemically (liver, kidney, and serum) and locally in the knee (joint tissues and synovial fluid) in animals treated with IV adMSCs relative to controls (as per enzyme‐linked immunosorbent assay and/or immunohistochemistry, dictated by tissue sample). Thus, systemic administration of adMSCs by IV injection significantly improved gait parameters and reduced both systemic and intra‐articular inflammatory mediators in animals with OA. These findings demonstrate the potential utility of alternative delivery approaches for cellular therapy of OA, particularly for patients with multiple affected joints.